(untitled) (Docentes 2.0 Journal, 2019)
The mediation of learning with the “game” resource is a current trend. The objective of the research was to determine the influence of gamification on student motivation and academic performance in the subjects of basic social and mathematical psychology. The methodology was based on descriptive research - comparative longitudinal cutting, using gamification based on the Marczewski methodology. The study sample was 30 students of the subjects in study of the psychology career of the Universidad Tecnológica Indoamérica (UTI), in which the "game" was applied as an independent variable and as dependent variables motivation and academic performance. The information analysis was performed in SPSS, applying descriptive and inferential statistics. The results from the point of content show that gamification was easily adapted to class plans. The CEAP 48 scale was applied for where the deep motivation of one of the subscales in the subject of social psychology verified a better trend; while, in mathematics it was superficial motivation. Regarding academic performance, an increasing behavior was observed in the two subjects in an approximate average of 2 points, according to Pearson’s correlation there is a ratio of 12% and 2% respectively, of the gamification on performance and modification.